2019
DOI: 10.1016/j.jpba.2018.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Authentication and discrimination of green tea samples using UV–vis, FTIR and HPLC techniques coupled with chemometrics analysis

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 15 publications
0
57
0
4
Order By: Relevance
“…These bands are characteristic of carbonyl groups derived from the conformational structures of MD and GA. Figure 2b shows all the treatments obtained, where it is possible to identify a third weak band at 327 nm. According to reports, this band is attributed to the presence of PC such as catechins, flavonoids and phenolic acids [43]; these phytoconstituents are characterized by the presence of various chromophores and conjugated systems that act as UV-absorbing systems. The presence of anthocyanins from Hibiscus was evidenced in the band at 532 nm [1].…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
See 1 more Smart Citation
“…These bands are characteristic of carbonyl groups derived from the conformational structures of MD and GA. Figure 2b shows all the treatments obtained, where it is possible to identify a third weak band at 327 nm. According to reports, this band is attributed to the presence of PC such as catechins, flavonoids and phenolic acids [43]; these phytoconstituents are characterized by the presence of various chromophores and conjugated systems that act as UV-absorbing systems. The presence of anthocyanins from Hibiscus was evidenced in the band at 532 nm [1].…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…The activity for the DPPH radical, attributed to the solvent of extraction (water) and the extract: carrier ratio (1:1); when the encapsulate containing a smaller amount of carrier agents there are more hydroxyl groups available to react with the DPPH radical [43]. As well, this can be influenced by the condensed tannins derived from the heat treatment of calyces, since they exhibit a good (DPPH) AOX capacity mainly due to the tannins and flavonoids containing a variety of hydroxyl groups that show stronger AOX and elimination of free radicals of the PC present (see Supplementary Materials Table S2 and Figure S1) [48].…”
Section: Pc Content and Aox In Hibiscus Encapsulatesmentioning
confidence: 99%
“…For catechins monomers, the content of EGCG was the highest in all samples. EGCG, EGC, ECG, and EC represent the main catechins in green tea [ 19 , 20 ]. The lower the sample grade, the higher the contents of EGCG, EC, EGC, and GCG, which is consistent with the results reported by Pan [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers also used these digital instruments for tea classification. Aboulwafa et al found that the PCA plot of UV spectroscopic data can be used to separate two areas: low-quality Chinese tea, high-quality Chinese tea, and entire South Asian samples (from India and Sri Lanka) [ 20 ]. Dankowska and Kowalewski reported UV-Vis spectroscopy with PCA to identify six tea types; however, there were overlapping areas [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Figure 2b shows all the treatments obtained, it was possible to identify a third weak band at 327 nm. According to reports, this band is attributed to the presence of PC such as catechins, flavonoids and phenolic acids [30]; this phytoconstituents are characterized by the presence of various chromophores and conjugated systems that act as UV-absorbing systems. The presence of anthocyanins from Hibiscus was evidenced in the band at 532 nm [1].…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%